Value of serum thiol/disulphide in chronic prostatitis - Öncel, Halil Ferat; Salar, Remzi; Özbay, Engin; Dikici, İbrahim Halil; Demir, Mehmet; Verit, Ayhan (Journal of Surgery and Medicine, 2021)
Background/Aim: Thiols are an important part of the antioxidant system which destroy reactive oxygen molecules, especially in inflammatory reactions. Maneuvers expressing the prostate fluid required for the diagnosis of chronic prostatitis are not practical and are rarely used in clinical practice. We aimed to compare the level of native thiol/disulphide as a supportive biomarker in patients with chronic abacterial prostatitis. Materials and methods: Twenty patients diagnosed with chronic prostatitis and 20 healthy volunteers were included in this prospective-case control study. Both groups were compared in terms of native thiol disulphide homeostasis, IPSS, QoL and PSA levels. Results: In the chronic prostatitis group, the native thiol level was significantly lower (P=0.043), the %disulfide/natural thiol was higher (P=0.037), the international prostate symptom score was higher (P=0.006), the quality of life was higher (P=0.023) and the maximum flow rate was lower (P=0.009) compared to the healthy volunteers. Conclusion: In this study, we found that the native thiol (SH) level in patients with chronic prostatitis was low and their disulphide level was high; therefore, we think that the level of native thiol/total thiol may assist in supporting the diagnosis of chronic prostatitis.